Perceived intrusiveness, consumer attention, and intent to purchase: The moderating effect of celebrity preferences - Tiara Nur Anisah; Miswanto Miswanto (Universitas Sebelas Maret, 2021)
This study aims to investigate the moderating effect of celebrity preferences on the relationship between perceived intrusiveness, consumer attention, and intent to purchase by applying Stimulus-Organism-Responds (SOR) Theory as a foundation. A total of 310 questionnaires were used in this study. This study uses the Structural Equation Modelling (SEM) Analysis approach by dividing a sample into two groups: (1) preference and (2) non-preference. A total of 155 samples filled out advertisements that matched respondents’ preferences and 155 samples filled out advertisements that did not match respondents’ preferences. The finding of this study are: (a) perceived intrusiveness is negatively affects consumer attention, (b) consumer attention positively affect intent to purchase, (c) celebrity preference moderates the effect of perceived intrusiveness on consumer attention, in a way that the higher celebrity preference will reduce the effect of perceived intrusiveness on consumer attention, and (d) celebrity preference moderates the influence of consumer attention on intent to purchase, in a way that the higher celebrity preference will strengthen the influence of consumer attention on intent to purchase. This finding could indicate the presence of intrusive advertising if the ad matches the preferences of the audience, then the ad will still get the attention of the audience and even affect the consumer's intention to buy.